Data classification by parallel generation of set partitions. (1st January 2013) - Thanh, Hoang Chi
In this paper, we propose two data classification problems. As each crisp classification of a data object set is a partition of the set, so we apply our partition generation algorithm to the data classification problems. First, we recall our new simple algorithm generating partitions and parallelise it. Then we separate a data object set into classes by partitioning the set.